2019
DOI: 10.1093/comjnl/bxz057
|View full text |Cite
|
Sign up to set email alerts
|

On Equivalence of Cascade Connections of Two Nonlinear Feedback Shift Registers

Abstract: Grain is a hardware-oriented finalist in the eSTREAM Stream Cipher Project. As a particular Galois nonlinear feedback shift register (NFSR), cascade connection of two NFSRs has been used as the main building block in the Grain family of stream ciphers. Two NFSRs are said to be equivalent if their sets of output sequences are equal. Finding properties of equivalent cascade connections of two NFSRs is useful to the design of the Grain family of stream ciphers. This paper first gives some properties of feedback f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Instead of considering general decomposition, a practical algorithm has been proposed to find * -factors for the special case FSRðhÞ: ¼ FSRðgÞ: * FSRðgÞ: [18]. Zhong and Lin [19] gave strong results on uniqueness of cascade decomposition FSRð f Þ: * FSRðgÞ: . Additionally, the periods of sequences generated by the grain-like structures are studied [20][21][22][23][24].…”
Section: Iet Information Securitymentioning
confidence: 99%
“…Instead of considering general decomposition, a practical algorithm has been proposed to find * -factors for the special case FSRðhÞ: ¼ FSRðgÞ: * FSRðgÞ: [18]. Zhong and Lin [19] gave strong results on uniqueness of cascade decomposition FSRð f Þ: * FSRðgÞ: . Additionally, the periods of sequences generated by the grain-like structures are studied [20][21][22][23][24].…”
Section: Iet Information Securitymentioning
confidence: 99%
“…Stream cipher design can benefit from examining the features of two equivalent cascade NFSRs, for example, to choose a better NFSR based on its quality metrics [69] showed that for any given cascade connection of an m-stage NFSR1 into an n-stage NFSR2, there exists only another one equivalent cascade connection of an m-stage NFSR3 into an n-stage NFSR4.…”
Section: The Equivalence and Decomposition Between Cascade Nfsrsmentioning
confidence: 99%
“…These results are more novel than previous conclusions and are very helpful for the design of practical stream cipher algorithms and decoding algorithms. According to the specific research object, the main achievements can be roughly divided into the modeling of NFSRs [65][66][67], the analysis of the structure of NFSRs [68][69][70][71][72][73][74][75][76][77][78][79][80][81], and the study of the properties of NFSRs [82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97]. This paper will give an overview of the latest achievements in NFSR research based on STP from these three aspects.…”
Section: Introductionmentioning
confidence: 99%